Lifestyle, Oxidative Stress, and Antioxidants: Back and Forth in the Pathophysiology of Chronic Diseases - Sharifi-Rad, Mehdi; Anil Kumar, Nanjangud V.; Zucca, Paolo; Varoni, Elena Maria; Dini, Luciana; Panzarini, Elisa; Rajkovic, Jovana; Tsouh Fokou, Patrick Valere; Azzini, Elena; Peluso, Ilaria; Prakash Mishra, Abhay; Nigam, Manisha; et al. (Frontiers in Physiology, 2020)
Oxidative stress plays an important role in the pathogenesis of chronic diseases such as cardiovascular diseases, diabetes, neurodegenerative diseases, and cancer. Long term exposure to increased levels of pro-oxidant factors can cause structural defects at 2 of mitochondrial DNA level, functional alteration of several enzymes and cellular structures leading to aberrations in gene expression. The modern lifestyle associated with processed food, exposure to a wide range of chemicals and lack of exercise plays an important role in oxidative stress induction. In the last decade, the use of medicinal plants with antioxidant properties has been exploited for their ability to treat or prevent several human pathologies in which oxidative stress seems to be one of the causes. Besides the broad spectrum of positive effects reported in the literature, some negative results have also been described. In this review are discussed the diseases in which oxidative stress is one of the triggers and the plant-derived antioxidant compounds with their mechanisms of antioxidant defences that can help in the prevention of these diseases. Finally, both beneficial and detrimental effects of antioxidant molecules used as therapeutic agents to reduce oxidative stress in several human diseases are carefully analysed.